Multidisciplinary Partnership to Upgrade Patient Satisfaction and Healthcare Performance - Al-huqayl, Abdullah Mohammed Solaiman; Alshahrani, Abdullah Saad Hussein; Alqahtani, Amer Saeed Saad; Alharthi, Fatema Saeed; Aljohani, Abdullah Heleil; Mudeife, Khlood Ahmed; Darraj, Siddiq Harban Bin Siddiq; Alshihabi, Ali Mohammad Hassan; Alzaid, Nourah Mohammed; Alshahrani, Ashwaq Mesfer; Aldossari, Haya Belal; Aldosary, Ohoad Bilal (Journal of Ecohumanism, 2024)
Healthcare systems today demand a collaborative approach to meet the rising expectations of patient satisfaction and healthcare performance. This article examines the pivotal roles of Medical Device Specialists, Radiology Technologists, Midwives, Family Medicine Practitioners, Anesthesia Technicians, Medical Secretaries, Health Services Managers, and Nursing Scientists in achieving these goals. Each profession contributes distinct expertise that ensures high-quality, patient-centered care across various healthcare settings. Through a synergistic partnership, these roles address complex challenges such as workflow efficiency, diagnostic precision, and patient safety. The review provides actionable strategies for fostering multidisciplinary teamwork, optimizing healthcare delivery, and enhancing clinical outcomes.